ASSESSMENT AND OUTCOME ON PREPARATIONS, CHARACTERIZATION OF TOPICAL TARGETED NANOSPONGE BASED DRUG DELIVERY: CRITICAL REVIEW - burad, shruti; Markad, Karishma; Kulkarni, Nilesh; Dhole, Shashikant (Asian Journal of Pharmaceutical and Clinical Research, 2023)
The pharmaceutical Industry, and most of the drugs which come from synthetic chemistry possess poor water solubility and approximately 70% of drugs fall under such category. To improve solubility, drug absorption and bioavailability are a critical lookout for the formulation scientist. The current research activity for the development of dosage forms is concentrated on the development of particulate carrier systems such as microspheres and liposomes. Nanosponge is being prioritized to control the delivery of drug/APIs/phytoconstituents to particular the skin targetting. The drug delivery to skin can be prevented through the development of nanosponge. Topical nanosponge preparation can be delivered in the form of local anesthetics, anti-fungal, anti-acne, anti-wrinkle, etc. drugs. The present study highlights the developmental stages for the topical targeted nanosponge drug delivery. The review covers a different method of preparation, and evaluation of topical nanosponge drug delivery systems.